Comportamento físico e mecânico de compósitos feitos de matriz de polietileno verde reforçados por longas fibras de bambu: influência do tratamento físico e químico das fibras nas fibras e nos compósitos - Costa, Milene Muniz Eloy da (2019)
The environmental concern with the unregulated use of non-renewable resources, as well as the inadequate disposal of waste in the environment, encourage the development of awareness measures and technological alternatives. Faced with this problem, there is a need to manufacture products that are less aggressive to the environment, either according to their raw material or according to their post-use. The use of natural fibers applied as reinforcement in polymeric matrices is an alternative for the manufacture of industrial products in various areas, from household utensils and packaging to civil construction products. The choice of bamboo fibers was motivated by the use of a long fiber vegetable source reinforcement, with good mechanical strength, low density and low cost. In addition, the work proposes the use of a polymeric matrix produced from a renewable plant source, sugar cane. In this context, the proposal of this thesis was to develop a composite produced entirely from renewable sources, evaluating its applicability through characterization and investigation of some morphological, physicochemical and mechanical properties of bamboo fibers, green polyethylene matrix and produced composites, and, mainly, evaluating the effect of different treatments performed on fibers on the composites mechanical properties. The morphological and physicochemical characterizations revealed a decrease in fiber mass after treatments, as well as variations in density, porosity and pore size. Also an increase of roughness at the fibers surface was observed, suggesting an improved mechanical anchorage by the polymeric matrix. The tensile tests showed that the mechanical properties (modulus of elasticity and tensile strength) of the fibers were improved with some treatments. The mechanical characterization of the composites highlighted that the treatments were effective for a good adhesion between fiber and polymer matrix. To conclude, the experimental investigations showed that the best treatments were mercerization and acetylation, indicating that the produced composites have applicability for projects which, at a high loading rate, they support fragile fracture.